2023
DOI: 10.2147/idr.s406243
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein Inhibits the Staphylococcus aureus Biofilm and the LuxS/AI-2 System in vitro

Abstract: Introduction Staphylococcus aureus ( S. aureus ) is a common cause of mastitis in dairy cows, a condition that has a significant economic impact. S. aureus displays quorum sensing (QS) system-controlled virulence characteristics, like biofilm formation, that make therapy challenging. In order to effectively combat S. aureus , one potential technique is to interfere with quorum sensing. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…aureus and E. coli are commonly found in BAI. , In the bacterial fouling tests (Figure a), the attachment percentage on the coatings was determined with respect to the bacterial number on the bare substrate. Representative fluorescence images for bacterial adsorption on bare and ME91-modified steel are shown in Figure S2.…”
Section: Resultsmentioning
confidence: 99%
“…aureus and E. coli are commonly found in BAI. , In the bacterial fouling tests (Figure a), the attachment percentage on the coatings was determined with respect to the bacterial number on the bare substrate. Representative fluorescence images for bacterial adsorption on bare and ME91-modified steel are shown in Figure S2.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, this indicates that baicalin has a significant eradicating effect on preformed biofilms of A.lwoffii . In addition, some studies have shown that baicalin with a certain concentration can eradicate mature biofilm of bacteria [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then, the extracted peak information was compared with databases including the HMDB, MassBank, and Bioprofile's local self-built metabolite standards library for a full library search. Multivariate analyses were also performed, including principal component analysis (PCA), partial least squares discriminant analysis (PLS-DA), cluster analysis, and differential metabolite screening [primers are listed in Supplementary Table 1 (27)].…”
Section: Discussionmentioning
confidence: 99%